2007
DOI: 10.1111/j.1365-3040.2007.01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in pea (Pisum sativum L.) demonstrates the importance of root but not shoot C/N ratios in the control of plant morphology and reveals a unique relationship between shoot length and nodulation intensity

Abstract: Nodule numbers are regulated through systemic autoregulatory signals produced by shoots and roots. The relative effects of shoot and root genotype on nodule numbers together with relationships to organ biomass, carbon (C) and nitrogen (N) status, and related parameters were measured in pea (Pisum sativum) exploiting natural genetic variation in maturity and apparent nodulation intensity. Reciprocal grafting experiments between the early (Athos), intermediate (Phönix) and late (S00182) maturity phenotypes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…The genetic variability in Ndfa, [N], and C/N ratio in soybean is not well defined (Ludidi et al, 2007; Yoneyama et al, 2000); however we were able to identify multiple genomic loci likely associated with each trait (Table 5; Fig. 7).…”
Section: Discussionmentioning
confidence: 96%
“…The genetic variability in Ndfa, [N], and C/N ratio in soybean is not well defined (Ludidi et al, 2007; Yoneyama et al, 2000); however we were able to identify multiple genomic loci likely associated with each trait (Table 5; Fig. 7).…”
Section: Discussionmentioning
confidence: 96%
“…However, it has been reported that the balance between C and N availability is important in determining the relationship between the allocation of biomass to roots and shoots (Ludidi et al 2007). Across all treatments, P. yunnanensis allocated their dry matter between shoots and roots largely in relation to its internal C/N status, as can be seen from the significant linear relationships between Rs and C/N ratios in stems and roots, suggesting that the root-to-shoot partitioning is controlled by some aspect of the plant's C and N balance (Ludidi et al 2007). While the C/N ratios in stems and roots were correlated with Rs across all treatments, interestingly, C/N in leaves was largely independent of Rs.…”
Section: Discussionmentioning
confidence: 99%
“…Then, seeds were pre-germinated in trays including sterile mixture of vermiculite and perlite. Then, 3 days old germinated seeds were transplanted into the pots (3 L) with 2 kg pot -1 sterile soil (pH 5.6, N 7 mg/L, P 13 mg/L, and K 2 O 120 mg/L) as described in our previous study ( Desalegn et al, 2016 ) and placed under controlled environmental conditions (14-h day/10-h night; 600 μmol m -2 s -1 light intensity; 22°C/16°C day/night temperature; 60–70% relative humidity) ( Ludidi et al, 2007 ; Larrainzar et al, 2014 ). All NR plants were fertilized once a week with 200 mL of Broughton and Dilworth nutrient solution ( Broughton and Dilworth, 1970 ; Laguerre et al, 2007 ) containing 10 mM KNO 3 .…”
Section: Methodsmentioning
confidence: 99%